2014
DOI: 10.1159/000362782
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic/Ischemic and Infectious Events Have Cumulative Effects on the Risk of Cerebral Palsy in Very-Low-Birth-Weight Preterm Infants

Abstract: Background: Hypoxia/ischemia and inflammation are two major mechanisms for cerebral palsy (CP) in preterm infants. Objective: To investigate whether hypoxia/ischemia- and infection-related events in the perinatal and neonatal periods had cumulative effects on CP risk in very-low-birth-weight (VLBW) premature infants. Methods: From 1995 to 2005, 5,807 VLBW preterm infants admitted to Taiwan hospitals were enrolled.The cumulative effects of hypoxic/ischemic and infectious events during the perinatal and neonatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…HI and infection/inflammation are the 2 major risk factors for WMD in VLBW preterm infants [1, 16, 17]. However, clinical and experimental evidence suggests that systemic infection or inflammation is not enough to induce obvious central nervous system lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HI and infection/inflammation are the 2 major risk factors for WMD in VLBW preterm infants [1, 16, 17]. However, clinical and experimental evidence suggests that systemic infection or inflammation is not enough to induce obvious central nervous system lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al [3] previously demonstrated that Xe upregulated the prosurvival proteins Bcl-2 and brain-derived neurotrophic factor (BDNF) to ameliorate brain injury in asphyxiated rats. Bcl-2 and Bcl-XL prevent apoptosis by regulating the mitochondrial membrane potential, and thereby blocking cytochrome c release into the cytosol [17]. Therefore, it is plausible to state that Xe mediates its neuroprotective effects via upregulating the level of the antiapoptotic gene Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…After obtaining parental consent, the infants were recruited for perinatal conditions and neonatal complications. Follow-up examinations were performed at a corrected age of 24 months [14]. On follow-up, pediatricians performed neuromotor examinations, while psychologists administered the Bayley Scales of Infant Development II [15].…”
Section: Methodsmentioning
confidence: 99%
“…Infants without cPVL and IVH served as the reference group. At the 24-month follow-up, CP was diagnosed on the basis of abilities and limitations in gross motor function using an algorithm-based classification [14]. Developmental delay was defined as the mental development index <70 by the Bayley Scales.…”
Section: Methodsmentioning
confidence: 99%
“…Case files included sociodemographic backgrounds, perinatal conditions, and neonatal complications [6, 7]. Parent consent was obtained, and the Taiwan Joint Institutional Review Board approved this study.…”
Section: Methodsmentioning
confidence: 99%